(untitled) (Fiep Bulletin - online, 2012)
Working with physical education for the Night School began in 2009 when a group of students of Physical Education FCT wanted to develop activities in this period and thereafter, with the support of a High School, implemented a service project to this layer of young students. From 2010, the project was approved by the Center for Teaching and looked Unesp with two scholarships for students to develop activities at the school. The main objective of this work is to provide opportunities for physical education classes in context with the proposal of the State Department of Education (2008) which launched the Network for teaching grants methodological teaching physical education from the design theory of the culture of body movement. The strategy of action was drawn up a roadmap of activities according to the needs of each classroom and the meetings were twice a week. At each meeting was applied a different theme of the Curriculum Proposal, using resources such as videos, photos, images, texts and explanations of educational activities. Attending these meetings was nine rooms School Night. As a result it appears that the participation of the rooms was satisfactory and the students interacted with the activities. Among the participating students, had a different repertoire and demonstrated knowledge of sports activities. The project is well accepted in the school which enables us to understand the needs of physical education classes at night.